Comparative Trade Analysis Between Indonesia and Organization Islamic Country - Nurul Azizah Az Zakiyyah Az Zakiyyah; Indanazulfa Qurrota A’yun A’yun; Firsty Ramadhona Ramadhona; Amalia Lubis Lubis (Islamic Economics Journal, 2022)
Globalization that took place in the last few decades has caused various changes in the world economic order. This effort was also carried out by Muslim countries with the aim of improving economic relations and coordination at the regional level so that the Organization of Islamic Cooperation (OIC) was formed. This study analyzes the comparative advantage and trade patterns between Indonesia and the OIC countries which are limited by 10 OIC member countries which have the largest average export value from Indonesia over the last ten years. These countries include Bangladesh, Iran, Malaysia, Nigeria, Egypt, Pakistan, Jordan, Saudi Arabia, Turkey and the United Arab Emirates. Data analysis in this study uses a quantitative approach. In this study, statistical software tools will be used, namely Microsoft Excel to calculate RCA, RSCA and also trading patterns of the 10 OIC countries with the largest trade volume, Indonesia tends to have a comparative advantage in products of Animal or vegetable fats and oils and their cleavage (HS 15) and Man-made staple fibers (HS 55) where these products are products that have a comparative advantage in the ten countries. Indonesia managed to maintain the same comparative advantage in 2005 and 2020 against the United Arab Emirates (UAE) where the superior product group in those 2 years was exactly the same and only changed its ranking position.